Elucidating factors contributing to disparities in pain-related experiences among adults with or at risk for knee osteoarthritis - Mickle, Angela M.; Domenico, Lisa H.; Tanner, Jared J.; Terry, Ellen L.; Cardoso, Josue; Glover, Toni L.; Booker, Staja; Addison, Adriana; Gonzalez, Cesar E.; Garvan, Cynthia S.; Redden, David; Staud, Roland; et al. (Frontiers in Pain Research, 2023)
We and others have reported ethnic/race group differences in clinical pain, physical function, and experimental pain sensitivity. However, recent research indicates with consideration for socioenvironmental factors, ethnicity/race is not significant. Understanding of factors contributing to pain inequities are needed. Guided by the NIA and NIMHD Health Disparities Research Frameworks, we evaluate the contributions of environmental and behavioral factors on previously reported ethnic/race group differences in: 1)clinical pain, 2)physical function, and 3)experimental pain in individuals with knee pain. Baseline data from Understanding of Pain and Limitations in Osteoarthritis Disease (UPLOAD) and UPLOAD-2 studies were analyzed. Participants were adults 45-85 years old who self-reported as non-Hispanic white (NHW) or black (NHB) with knee pain. A health assessment and quantitative sensory testing were completed. Measures including sociodemographics, environmental, health, clinical and experimental pain, and physical functioning were included in nested regressions. Pooled data from 468 individuals, 57±8 years of age, 63% women, and 53% NHB adults. As NHB adults were younger and reported greater socioenvironmental risk than the NHW adults, the term sociodemographic groups is used. With inclusion of recognized environmental and behavioral variables, sociodemographic groups remained a significant predictor accounting for <5% of the variance in clinical pain and physical function and <10% in experimental pain measures. The incorporation of environmental and behavioral factors reduced relationships between sociodemographic groups and pain-related outcomes. Pain sites, BMI, and income were significant predictors across multiple models. The current study adds to a body of research on the complex factors contributing to disparities in pain-related outcomes.